Assessment of Drainage Efficiency in the Backfill Disposal Area of East Air Laya Mine Field at PT. Bukit Asam; A case study from Tanjung Enim, South Sumatera, Indonesia - Fitri Indah Dwi Suci; Yazid Fanani; Yudho Dwi Galih Cahyono (Lembaga Penelititan dan Pengabdian kepada Masyarakat - Institut Teknologi Adhi Tama Suraba, 2024)
This research undertakes a thorough evaluation of the drainage systems in the disposal areas at PT. Bukit Asam during the October 2023 sequence, with the objective of understanding the factors that influence the capacity and efficiency of disposal mounds, the density of materials used, the geometric structure of disposal sites, and the design dimensions of open drainage channels. Utilizing the trapezium volume formula, the study meticulously calculated the planned disposal volumes at various elevations—2,289,155 Bank Cubic Meters (BCM) at 36 meters, 1,004,112 BCM at 42 meters, and 669,892 BCM at 48 meters—comparing these against an actual obtained volume of 1,799,111.4 BCM. The substantial variance between the planned and actual volumes highlights the critical challenges in achieving predictive accuracy in disposal management. Further assessments were conducted using the Dynamic Cone Penetrometer (DCP) with a 60-degree cone to determine the density and sub-grade California Bearing Ratio (CBR) of the barrier materials, which were found to be suitable for road construction, falling under sub-grade C classification. Moreover, the Gumbel method was applied to devise the dimensions of a trapezoidal open channel, designed to facilitate a drainage capacity of 100,432.996 cubic meters per hour over a length of 3000 meters. The channel dimensions included a bottom width of 1.1 meters, a top width of 2.3 meters, a depth of 2.4 meters, and a 45-degree slope, with a Manning’s coefficient (n) of 0.03. This detailed inquiry not only provides vital insights into the operational adjustments required for effective drainage but also promotes the adoption of sustainable and safe disposal management practices in the mining industry. The findings from this study serve as a pivotal reference for future improvements in the design and management of mine waste disposal systems